2019
DOI: 10.1148/radiol.2019182457
|View full text |Cite
|
Sign up to set email alerts
|

Local Tumor Staging of Breast Cancer: Digital Mammography versus Digital Mammography Plus Tomosynthesis

Abstract: Background: Combined digital mammography (DM) and digital breast tomosynthesis (DBT) (hereafter, DM plus DBT) has increased cancer detection rates when compared with those achieved with DM-only screening. However, there is limited literature on DBT as an adjunct to mammography in the staging of known breast cancers. Purpose: To compare the diagnostic accuracy of DM alone with that of DM plus DBT in the identification of additional ipsilateral and contralateral lesions in women with newly diagnosed breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…After labeling the carcinoma, mammographic control is recommended. Ultrasound (US) is effective in recognizing X-ray negative lobular breast carcinoma, but with multicentric and bilateral tumor spread characteristic for lobular breast carcinoma, the effectiveness of US is reduced [17,22,25].…”
Section: Sonography a Known Technique For Tumormentioning
confidence: 99%
“…After labeling the carcinoma, mammographic control is recommended. Ultrasound (US) is effective in recognizing X-ray negative lobular breast carcinoma, but with multicentric and bilateral tumor spread characteristic for lobular breast carcinoma, the effectiveness of US is reduced [17,22,25].…”
Section: Sonography a Known Technique For Tumormentioning
confidence: 99%
“…In this issue of Radiology, Fontaine and colleagues report outcomes from their prospective multicenter trial on the role of tomosynthesis in breast cancer diagnosis and staging (8). The authors identified 166 women with breast cancer who underwent digital mammography, DBT, and breast MRI to evaluate for additional disease.…”
mentioning
confidence: 99%
“…In the study by Fontaine et al (8), the improved diagnostic performance of tomosynthesis and digital mammography for additional breast cancers was limited to women with nondense breasts. This result may seem counterintuitive, given that tomosynthesis is known to improve visualization of breast cancer by reducing the effects of tissue superimposition, particularly in women with dense breasts.…”
mentioning
confidence: 99%
See 2 more Smart Citations